2020
DOI: 10.3329/jbas.v44i1.48564
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Multiple Rare Earths and Other Associated Elements in Zircon by Laser-Induced Breakdown Spectroscopy

Abstract: Laser-induced breakdown spectroscopy (LIBS), which is a powerful technique for the detection of minor and trace elements in a sample, has been used to analyze the enriched zircon mineral collected from the beach sands of southern Bangladesh. In addition to zirconium, a large number of rare earth elements viz. cerium, lanthanum, praseodymium, neodymium, ytterbium, gadolinium, dysprosium, erbium, samarium, europium, holmium and yttrium and other associated elements like hafnium, niobium, tantalum, magnesium, cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Whereas most of these works are associated with the detection of REEs in commercially available samples, Abedin et al [184] reported the first multiple rare earth (Ce, La, Pr, Nd, Y, Yb, Gd, Dy, and Er) detection in a naturally occurring monazite mineral by SP-LIBS (Figure 12). Likewise, Haider and Khan [185] detected multiple rare earth (Ce, La, Pr, Nd, Yb, Gd, Dy, Er, Sm, Eu, Ho, and Y) in an enriched zircon sample by SP-LIBS. e same group also identified trace REEs (Nd, Yb, Sm, Ce, Dy, and Gd) in coal samples collected from coal mines of Bangladesh (Barapukuria) and India (Meghalaya) [186].…”
Section: Detection Of Rare Earth Elements (Rees)mentioning
confidence: 93%
“…Whereas most of these works are associated with the detection of REEs in commercially available samples, Abedin et al [184] reported the first multiple rare earth (Ce, La, Pr, Nd, Y, Yb, Gd, Dy, and Er) detection in a naturally occurring monazite mineral by SP-LIBS (Figure 12). Likewise, Haider and Khan [185] detected multiple rare earth (Ce, La, Pr, Nd, Yb, Gd, Dy, Er, Sm, Eu, Ho, and Y) in an enriched zircon sample by SP-LIBS. e same group also identified trace REEs (Nd, Yb, Sm, Ce, Dy, and Gd) in coal samples collected from coal mines of Bangladesh (Barapukuria) and India (Meghalaya) [186].…”
Section: Detection Of Rare Earth Elements (Rees)mentioning
confidence: 93%
“…Long et al [90] recently proposed a data selection method for the reduction of matrix effects and signal uncertainty and to improve repeatability during LIBS analysis. LIBS was used for the detection of REEs and associated elements including nonmetals, like Si and P in the beach sands of southern Bangladesh [91]. LIBS can be used for automatic coal-rock recognition with 97% accuracy when combined with an artificial neutral network in coal quality testing during unmanned coal mining operations [92].…”
Section: Inductively Coupled Plasma-optical Emission Spectrometry (Ic...mentioning
confidence: 99%